2022
DOI: 10.18632/aging.203793
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-2 regulates 5-Fu resistance via the ERK/MAPK signaling pathway in colorectal cancer

Abstract: 5-Fluorouracil (5-Fu) is the first-line chemotherapeutic option for colorectal cancer. However, its efficacy is inhibited by drug resistance. Cytokines play an important role in tumor drug resistance, even though their mechanisms are largely unknown. Using a cytokine array, we established that tissue inhibitor metalloproteinase 2 (TIMP-2) is highly expressed in 5-Fu resistant colorectal cancer patients. Analysis of samples from 84 patients showed that elevated TIMP-2 expression levels in colorectal patients we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…The prognosis of CRC patients after radiotherapy and chemotherapy varies significantly, which may be closely related to the development of therapy resistance [14]. Although many studies have been devoted to finding predictive markers of chemoradiotherapy resistance in patients with CRC, no reliable markers have been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of CRC patients after radiotherapy and chemotherapy varies significantly, which may be closely related to the development of therapy resistance [14]. Although many studies have been devoted to finding predictive markers of chemoradiotherapy resistance in patients with CRC, no reliable markers have been widely used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Further study also shows that dasatinib exhibits modest antitumor effect only when combined with chemotherapy in CRC PDX 88 . It is reported that TIMP‐2 (tissue inhibitor of matrix metalloproteinase‐2) is upregulated in 5‐Fu‐resistant CRC PDX, and inhibition of TIMP‐2 using an anti‐TIMP‐2 antibody or ERK/MAPK (extracellular regulated protein kinase/mitogen‐activated protein kinase) inhibition by U0126 suppresses TIMP‐2‐mediated 5‐Fu‐resistance 89 . The ATM (ataxia telangiectasia‐mutated gene) inhibitor, AZ31, exhibits antitumor activity in CRC PDX resistant to irinotecan monotherapy 90 .…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%
“…88 It is re- U0126 suppresses TIMP-2-mediated 5-Fu-resistance. 89 The ATM (ataxia telangiectasia-mutated gene) inhibitor, AZ31, exhibits antitumor activity in CRC PDX resistant to irinotecan monotherapy. 90 Alisertib, an inhibitor of aurora kinases, shows antitumor activity in combination with cetuximab or irinotecan.…”
Section: Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…The extracellular signal-regulated kinase/mitogen-activated protein kinase (ERK/MAPK) signaling pathway is activated in numerous cancers, including lung cancer, and is involved in regulating the proliferation, survival, invasion, apoptosis and drug resistance of cancer cells (9)(10)(11). In addition to being overactivated by RAS proteins, the ERK/MAPK signaling pathway is also overactivated by the α subtype of protein kinase C (PKCα) in cancer (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%